Antimicrobial Activity of Essential Oil of Baccharis dracunculifolia DC (Asteraceae) Aerial Parts at Flowering Period - Cazella, Luciane Neris; Glamoclija, Jasmina; Soković, Marina; Gonçalves, José Eduardo; Linde, Giani Andrea; Colauto, Nelson Barros; Gazim, Zilda Cristiani (Frontiers in Plant Science, 2019)
Baccharis dracunculifolia DC (Asteraceae) is a Brazilian native bush tree, and its leaf essential oil has been reported to possess some biological activities, but the antimicrobial activity of its aerial part essential oil at the flowering period is unknown or little studied, mainly against agents that cause foodborne diseases. Thus, this study aimed to determine the chemical composition and evaluate the antimicrobial activity of the essential oil of B. dracunculifolia aerial part at flowering period. This essential oil was obtained by hydro distillation and its chemical composition was determined by gas chromatography coupled with mass spectrometry (GC–MS). The minimum inhibitory concentration, minimum bactericidal concentration, and minimum fungicidal concentration of the essential oil were evaluated against eight bacteria and eight fungi using 96-well microtiter plates. The essential oil yield was 1.8 ± 0.07%, and spathulenol (27%) and trans-nerolidol (23%), both oxygenated sesquiterpenes, were the major compounds found among 30 chemical constituents identified. The essential oil presented bacteriostatic and bactericidal activities, mainly against Staphylococcus aureus, Bacillus cereus and Pseudomonas aeruginosa, and also fungistatic and fungicidal activities. However, its antibacterial activity was more effective than the antifungal one by using the essential oil at lower concentrations. Essential oil of B. dracunculifolia may be a potential alternative for food applications in order to reduce synthetic chemicals in a more sustainable food industry.